Racism as a condition for thinking the ethics of ethnic-racial relations in Basic Education (Práxis Educativa, 2022)
This article has as its object the racism generated by exclusion and aims to develop a reflection on the ethical formation about the education of ethnic-racial relations in school education, under the argument of what scientific investigations say about the level of awareness in relation to prejudice, violence and discrimination in Basic Education. Methodologically, a study was carried out on Hannah Arendt’s concepts of crisis, plurality and authority, and on Kabengele  Munanga’s concepts of race, racism, identity and ethnicity, through a survey of Master’s and Doctoral research sources. The analysis of the material showed the possibility of forging ethical pedagogical practices that contribute to developing social coexistence, fighting racism and establishing democracy, eliminating prejudice and racial discrimination.Keywords: Racism. Ethical education. Ethnic-racial relations.